Reviews of recent publications (Studies in 20th & 21st Century Literature, 2002)
Avelar, Idelber. The Untimely Present: Post-Dictatorial Latin American Fiction and the Task of Mourning by Herbert J. Brant Bertharion, Jacques-Denis. Poetique de Georges Perec by Warren Motte Cascardi, Anthony J. Consequences of Enlightenment by Holger Briel Cloonan, William. The Writing of War: French and German Fiction and World War II by Damon Rarick Holloway, Vance R. El Posmodernismo y otras tendencias de la novela espanola (1967-1995) by Nancy Vosburg O'Neill, Patrick. Gunter Grass Revisited by Stuart Taberner Smorkaloff, Pamela Maria. Cuban Writers On and Off the Island: Contemporary Narrative Fiction by Teresa R. Arrington
Keywords: Idelber Avelar; The Untimely Present: Post-Dictatorial Latin American Fiction and the Task of Mourning; Herbert J. Brant; Jacques-Denis Bertharion; Poetique de Georges Perec; Warren Motte; Anthony J. Cascardi; Consequences of Enlightenment; Holger Briel; William Cloonan; The Writing of War: French and German Fiction and World War II; Damon Rarick; Vance R. Holloway; El Posmodernismo y otras tendencias de la novela espanola (1967-1995); Nancy Vosburg; Patrick O' Neill; Gunter Grass Revisited; Stuart Taberner; Pamela Maria Smorkaloff; Cuban Writers On and Off the Island: Contemporary Narrative Fiction; Teresa R. Arrington